A structural equation method for improving customer satisfaction of e-commerce websites using the hybrid approach of QFD and WebQual. (30th September 2020) - Ershadi, Mohammad Javad; Sadeghi, Mojtaba; Azizi, Amir
The present study has provided a framework in order to improve the satisfaction of users of e-commerce sites using quality function deployment (QFD) and WebQual instruments. A structural equation model (SEM) has been developed in order to determine the significance of each aspect of the WebQual model and its significance weight. This study has evaluated the satisfaction of users with the quality of website content, transaction quality and security, usability and service interaction quality, and provided the solutions to improve these factors in form of the QFD method. Results showed the transaction quality and security has the highest priority for improvement. Among all the customers' requirements, the indicators such as a wide range of exchanges, preserving privacy, ease of transaction, the right format, ease of search, the usefulness of transactions, and finally the clear and understandable interactions should be placed in a higher priority for improvement by management.